2020
DOI: 10.34001/jmer.2020.6.01.1-1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship Between Earnings and Corporate Taxes on Dividend Policy of Companies in Sri-Kehati Index

Abstract: Objective: This study examines the effect of earnings and corporate taxes role on the company's dividend policy in the SRI-KEHATI Index. In this research, dividend policy means dividends paid proportion to shareholders. Earnings are estimated by four financial ratios namely contributed capital ratio, prior year-earnings, sales growth, and return on assets.Research Design & Methods: The sample is taken according to purposive sampling with the criteria of the consistency of the company listed in the SRI-KEHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, these companies are not involved in the negative use of pesticides, nuclear energy, weapons, tobacco, alcohol, pornography, gambling, genetic engineering of organisms, and coal exploitation. According to [17], good dividend policy governance boosts firm value. Meanwhile, for companies included in the green index, it is believed to support its contribution to SRI and ESG principles, specifically during crisis conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these companies are not involved in the negative use of pesticides, nuclear energy, weapons, tobacco, alcohol, pornography, gambling, genetic engineering of organisms, and coal exploitation. According to [17], good dividend policy governance boosts firm value. Meanwhile, for companies included in the green index, it is believed to support its contribution to SRI and ESG principles, specifically during crisis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fund management companies managed total assets worth more than IDR 2,500,000,000,000. This index creates opportunities for investors to invest in issuers that contribute to financial performance, as well as has an impact on the environment and its sustainability [17,31].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the first control variable was sales growth, which was an important indicator for management when deciding to pay dividend (Salvatori et al, 2020). This indicated that the companies with relatively stable sales levels easily generated profits, obtained funds, and had higher fixed costs than unstable organizations (Brigham & Houston, 2019).…”
Section: Control Variablementioning
confidence: 99%
“…A related study is recognized for the potential to enhance the value of a company. Meanwhile, the increase in value is an indicator of achieving the main objective (Ofori-Sasu et al, 2017, and the concept is believed to affect the economic growth of business activities (Giri & Joshi, 2017;Salvatori et al, 2020). In this context, the operations make a significant macroeconomic contribution by paying taxes.…”
Section: Introductionmentioning
confidence: 99%